2009
DOI: 10.4067/s0718-221x2009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Bending strength and stiffness of structural laminated veneer lumber manufactured from fast-growing Argentinean Eucalyptus grandis

Abstract: The present paper reports the results of an investigation regarding the determination of bending strength and stiffness in specimens of laminated veneer lumber (LVL) manufactured from Argentinean Eucalyptus grandis and tested edgewise according to European standards. For this purpose an empirical research project with one sample containing 44 specimens with nominal sizes of 24.3 mm in width, 100 mm in depth and 2.44m in length was carried out. The characteristic strength value was 74 % and 118 % higher, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…It can be observed that the glue line shear strength of all differently pressed LVL panels exceeds the minimum required by EN-314-2 (1 N/mm 2 ) [18]. Additionally, the modulus of rupture (MOR) was rather different from case to case with T6 showing bending strength on edge comparable to values reported in the literature [24]. The modulus of elasticity (MOE) values in Table 4 are similar to what found in the literature for cases T6 and T7, but lower for the other cases [24].…”
Section: Muf Resinmentioning
confidence: 60%
“…It can be observed that the glue line shear strength of all differently pressed LVL panels exceeds the minimum required by EN-314-2 (1 N/mm 2 ) [18]. Additionally, the modulus of rupture (MOR) was rather different from case to case with T6 showing bending strength on edge comparable to values reported in the literature [24]. The modulus of elasticity (MOE) values in Table 4 are similar to what found in the literature for cases T6 and T7, but lower for the other cases [24].…”
Section: Muf Resinmentioning
confidence: 60%
“…Arguably, the main drawback for the development of this industry is the lack of a market for the by-products of the mechanical transformation. Conversely, Eucalyptus grandis timber has also a strong potential to be used as raw material for engineered wood products, mainly due to its high ratio of modulus of elasticity to density (Piter et al 2007, Saviana et al 2009, and the presence of eucalyptus pulp mills in the country could potentially contribute to the development of high-valued wood products for the construction industry. In Uruguay, BEKP is obtained from a central forest product, eucalyptus pulp logs, with plantations destined exclusively for this purpose, but, in an integrated market, pulp can be produced from by-products of the mechanical transformation industry, increasing value adding Recently, the feasibility of the fabrication in China of CLT panels from eucalyptus originally cultivated for pulp production, was successfully assessed (Liao et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…LVL beams is an engineered wood product, used extensively in North America for the wood construction industry, which has been regionally tested for Eucalyptus grandis wood (Saviana et al 2009). Beams are composed of multilayers of rotary-peeled veneers, with their faces parallel to the wood grain, glued with PF resins and hot pressed.…”
Section: Methodsmentioning
confidence: 99%
“…has comparable physical and mechanical properties to that of LVL made of poplar, beech, and even Norway spruce [71,72]. Large faults can be avoided when logs are cut into thin veneers and assembled and glued parallel to the grain, which may explain why reported LVL values are typically higher than those achieved for other traditional hardwood products [73]. Bal and Bektas ¸ [74] stated that LVL is typically made from softwood species and low-and medium-density hardwood species with densities ranging from 290 to 693 kg.m −3 .…”
Section: Lvlmentioning
confidence: 99%